La contribución de la Historia de las Matemáticas a la Formación de Profesores de Matemáticas de Educación Secundaria - Hodgson, Bernard R. (2013)
In this paper, I discuss the place of history of mathematics in teacher education programmes, and more specifically the contribution that this topic may bring to the preparation of secondary school mathematics teachers. Taking as a basis the requirement more and more widespread in many countries of integrating elements of culture and history in the mathematics school curriculum, I examine how such a context impacts on university programmes for teacher education, as well as on the mathematics departments offering courses in the history of mathematics. I also present a few examples, taken from my own teaching to preservice secondary school teachers, of mathematical topics with a historical flavour.